Multifaceted microbial enzyme nattokinase: a comprehensive review on therapeutics applications, production technologies and intellectual property landscape - Tirth Chetankumar Bhatt; Viralkumar B. Mandaliya; Munir Ibrahim; Avani Bhimani; Asmita Detroja; Jaykumar Koradiya; Gaurav Sanghvi; Ashok Kumar Bishoyi (Current Research in Biotechnology)
Cardiovascular diseases (CVDs) have risen drastically after the COVID era as post-COVID symptoms. “Nattokinase” (NK), the thrombolytic enzyme, is known for its substrate-specific thrombolytic, protease, and fibrinolytic activity to ameliorate CVDs. Primarily, NK was isolated from Bacillus subtilis natto using either solid- or liquid-state fermentation technology. Later, the researchers studied the arpN gene, which encodes NK and is used in various biotechnological approaches with different hosts such as Bacillus spp., Escherichia coli, Lactobacillus spp., and Pichia pastoris. The global market potential of NK in treating CVDs has recently garnered attention, leading to a demand for bulk production and ultrapure forms of NK. This demand has put pressure on strain improvements and innovation in production technology. The patent scenario suggested that NK have been given more attention with 763 patents compared to streptokinase, staphylokinase and serratiopeptidase. This review critically examined the biotechnological aspects of NK in amelioration of CVDs, focusing on current production technologies, strain improvement strategies, protected NK innovations, and future research directions. It emphasizes the need for advanced approaches like CRISPR technology and novel production protocols to develop high-quality, ultrapure NK. It is also aligning with Sustainable Development Goal (SDG) 3: “Good Health and Well-Being.”